2015
DOI: 10.1080/00103624.2014.969402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Humic Acid on Root Development and Nutrient Uptake ofVicia fabaL. (Broad Bean) Seedlings Grown under Aluminum Toxicity

Abstract: Interactions of humic acid with development and uptake by seedlings of Vicia faba L., (cv. Eresen 87)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 68 publications
1
16
0
2
Order By: Relevance
“…2). These results are in compliance with other studies conducted with Fabaceae, with emphasis on Vicia faba (Büyükkeskin et al 2015) and alfalfa (Cui et al 2017). According to a study conducted by Chen et al (2014) with alfalfa plants whose roots were incubated with increasing Al doses, the use of 0.25 mM of Al has reduced the growth of this structure by more than 50%.…”
Section: Discussionsupporting
confidence: 92%
“…2). These results are in compliance with other studies conducted with Fabaceae, with emphasis on Vicia faba (Büyükkeskin et al 2015) and alfalfa (Cui et al 2017). According to a study conducted by Chen et al (2014) with alfalfa plants whose roots were incubated with increasing Al doses, the use of 0.25 mM of Al has reduced the growth of this structure by more than 50%.…”
Section: Discussionsupporting
confidence: 92%
“…Also, El-Ghamry et al,(2009) on faba bean they indicated that adding humic acid at 2000 ppm significantly increased N, P and crude protein of faba bean seeds. Furthermore, Büyükkeskin et al,(2015) on broad bean reported that adding HA increased the content of N, P and K of broad bean seeds. Moreover, Gad El-Hak et al,(2012) working on pea, they mentioned that N, P, K % obviously show highest values by spraying pea plants with humic acid at the high rate of 2.0 g/L .Similar results were obtained by Senesi and Loffredo (1994) on pea and Neri et al,(2002) and El-Hefny (2010) on cowpea.…”
Section: -Chemical Composition Of Dry Seedsmentioning
confidence: 99%
“…Although plants have evolved various antioxidant defense mechanisms to counter such damage ( Apel and Hirt, 2004 ; Madsen-Bouterse et al, 2010 ), heavy metals trigger various epigenetic mechanisms, including DNA methylation, histone modification, and the expression of non-coding RNAs ( Erturk et al, 2015 ) that regulate gene expression in multiple ways, especially under stress conditions ( Cheng et al, 2012 ). It has been reported that gene expression has significant correlations with epigenetic modifications such as DNA hypo- and hyper-methylation; likewise, various biological pathways (i.e., transcriptional gene silencing and transposable element inactivation) are also linked with phylogenetic developments ( Cheng et al, 2012 ; Büyükkeskin et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%